Gender Differences in Percutaneous Coronary Intervention Insights from the Coronary Angiography - Faizan Ahmed, Mohsin Shabir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The data from the prior studies have reported inconsistencies in the comorbidity burden, and baseline risk profile. Objective: The data provide insights into the sex difference in percutaneous coronary interventions. Study design: It is a retrospective study with statistical approach, conducted in the Department of Cardiology, Rehman Medical Institute Peshawar. Material and Methods: The study was conducted from December 2021 to May 2022. The 400 patients visited the cardiology department of the hospital were included in the study. The selected patients were enrolled in the coronary angiography. The data was collected from cardiology department of two hospitals and analyzed. The ethical and review committee of the hospital approved the study. The informed consent was taken from the selected patients. The data contains demographic features, baselines characteristics, hospital complications and PCI course. The patients having residual stenosis of less than 50% after balloon angioplasty were included in the groups rated as successful PCI groups. Results: Out of 400 patients taken from two hospitals there were 50% female. The women included in the study were 5 years older than the male patients. Women were on average 67 years old and men were 72 years old. Women in general had more cases of coronary angiography, also women were reported with cases like diabetes mellitus, and some of the cases reported congestive heart failure. The success of the procedure was more successful in case of women with 95% of female patients receiving successful procedure. Conclusions: The overview of sex linked variations in PCI was observed in this study. The hospital mortality was found to be high in case of women, there was also not significant differences found between hospital mortalities for NSTE-2CS in case of cardiogenic problems